A Cross Sectional Study on Types, Clinical Assessment and Management of Inguinal Hernia - Krishnan, Dhanakodi; Sabapathi, Sundaram Lakshmi; Raja, Kathermydeen Syed; Gunaseelan, Rajapandi; Rohithraj, Jayaraj (Indian Journal of Pharmacy Practice)
Background: Hernias can be due to a birth defect, an injury, or repeated strain on the tissue. An inguinal hernia occurs close to the groin area in the abdomen. They develop a bulge of abdominal contents into the left or right inguinal canal through an abdominal wall defect. The main aim was to determine the clinical characteristics and surgical procedure used in patients with Inguinal Hernia and analyze the drugs used in both the preoperative and postoperative management of Inguinal Hernia. Materials and Methods: It is a cross-sectional observational study conducted in the Department of Surgery at The Government Medical College and Hospital, Nagapattinam, for six months. Results: A total of 89 patients fulfilled the criteria for eligibility. Among those patients, 62 had Inguinal hernias, where males showed a higher predominance than females (p = 0.056). The average mean age of inguinal hernia patients was 51±13 years (p = 0.021). The most common type of inguinal hernia was an indirect variety with 48 patients (p = 0.059), which occurs mostly on the right side in 61.1% of male patients and 38.9% of female patients. Hernioplasty was the most widely used technique in surgical management; it also required a lesser number of hospital stays (1–11 compared to herniorrhaphy, 1–13), and analgesics were mostly given for both pre-operative and post-operative management. Conclusion: The problem with hernias is that they are often seen as a minor issue, but they are quite debilitating. Awareness campaigns can help show people that hernias should be taken seriously and can be prevented in earlier stages.
Keywords: Hernia; Inguinal Hernia; Surgical management; Hernioplasty